Sandalovina - terminologija, etimologija, lastnosti in raba - Torelli, Niko (Les (Ljubljana), 2001)
Brief details are given of the etimology of the name sandalwood and its confusing dualism. The anatomy, properties and use of true or white sandalwood(Santalum album) and red sandalwood (Pterocarpus santalinus) are described. Most probable red sandalwood (Pterocarpus santalinus) may have beenthe source of the sandalwood used in King Solomon`s temple.
Keywords: sandalovina; Santalum album; Pterocarpus santalinus; terminologija; terminology; etimologija; etymology; anatomija; lastnosti; uporaba